Imaging Biomarkers for Neurodegeneration in Presymptomatic Familial Frontotemporal Lobar Degeneration - Chen, Qin; Kantarci, Kejal (Frontiers in Neurology, 2020)
Frontotemporal Lobar Degeneration (FTLD) is a neurodegenerative disorder characterized by behavioral abnormalities, language impairment, and deficits of executive and motor functions. FTLD has a strong genetic background with about 30%-50% FTLD patients having an autosomal dominant pattern of inheritance with major mutations in the MAPT, GRN and the C9orf72 repeat expansion. These mutations could lead to neurodegeneration years before the onset of clinical symptoms. With potential disease-modifying treatments that are under development, noninvasive biomarkers that help determine the early brain changes in presymptomatic FTLD patients will be critical for tracking disease progression and enrolling the right participants into the clinical trials at the right time during the disease course. In recent years, there is increasing evidence that a number of imaging biomarkers show abnormalities during the presymptomatic stage. Imaging biomarkers of presymptomatic familial FTLD may provide insight into the underlying neurodegenerative process years before symptom onset. Structural magnetic resonance imaging (MRI) has captured cortical degeneration with a mutation-specific neurodegeneration pattern years before symptom onset in presymptomatic familial FTLD mutation carriers. Loss of white matter microstructural integrity on diffusion tensor imaging (DTI) was also reported in presymptomatic mutation carriers of FTLD. Furthermore, proton magnetic resonance spectroscopy (1H MRS), which allows a noninvasive assessment of brain biochemistry, has identified early neurochemical abnormalities in presymptomatic MAPT carriers. Positron emission tomography (PET) imaging has demonstrated glucose hypometabolism by [18F]-fluorodeoxyglucose (FDG)-PET in the presymptomatic stage of familial FTLD. As well, a novel PET ligand 18F-AV-1451 has been used in this group to evaluate tau binding in the brain. Promising imaging biomarkers for presymptomatic familial FTLD have been identified and assessed for specificity and sensitivity for accurate prediction of symptom onset and track disease progression during the presymptomatic stage when clinical measures are not useful. Furthermore, identifying imaging biomarkers for the presymptomatic stage is important for the design of potential disease-modifying trials. We review the recent progress in imaging biomarkers of the presymptomatic phase of familial FTLD and discuss the imaging techniques and analysis methods, with a focus on the utility and potential implication of these imaging techniques in specific mutation types.